In-depth phenotyping of cardiac diseases by MRI in HIV-positive people reveals diverse and independent forms of myocardial involvement. (25th November 2020) - Arendt, C; De Leuw, P; Haberl, A; Stephan, C; Vasquez, M; Arcari, L; Zhou, H; Zainal, H; Albrecht, M; Vogl, T; Zeiher, A; Nagel, E; et al.
Abstract: Background: It is increasingly recognised that non-ischaemic and ischaemic myocardial involvement represent important drivers of cardiac diseases in people living with HIV (PLWH). Non-invasive measurements with cardiac magnetic resonance (CMR) directly inform on the type of myocardial damage. Purpose: To screen for the prevalence and type of cardiovascular disease (CVD) in PLWH using stress CMR in a cohort with highly active antiretroviral therapy (HAART). Methods: This prospective cross-sectional study enrolled consecutive PLWH undergoing standardised evaluation for CVD using imaging. All participants underwent a standardised CMR protocol in a 3 Tesla scanner for function and volumes (cine), stress perfusion (regadenosone), scar (late gadolinium enhancement (LGE)), diffuse fibrosis (native T1-mapping) and oedema (native T2-mapping). Blood samples were additionally collected prior to CMR. Results: 141 participants were identified (n=32 in category C/AIDS). 16 patients had previously documented (n=23) myocardial diseases: myocarditis, n=1 non-obstructive coronary artery disease (CAD), n=8 myocardial infarction, n=3 congestive heart failure, n=3, and arrhythmia, n=8. Mean value for hs-cTnT, CRP and NT-proBNP was 9±18ng/l, 0.3±0.6mg/l and 104±229ng/l. 14 subjects had impaired LV-EF (<50%) and 35 presented borderline LV-EF (50–55%). Myocardial LGE was present in 28 patients: non-ischemic pattern, n=16, ischemic pattern, n=11, and both patterns, n=1. Two patients had relevant inducible ischaemia, whereas a pattern of microvascular disease (MVD) was found in 26 patients. 72 subjects had diffuse fibrosis and 25 had active inflammation. Elevated native T1/T2 was significantly associated with low (<350/μl), current, and initial CD4-count (χ 2 =5.317, p=0.021; χ 2 =3.841, p=0.050), just as with category C/AIDS (χ 2 =4.949, p=0.026). Native T2 showed a significant correlation with initial CD4-count (r=−0.252, p=0.008) and current NT-proBNP (r=0.190, p=0.030), but not with other laboratory values. Conclusions: CMR in PLWH reveal high prevalence of cardiac involvement, which is predominantly non-ischaemic inflammatory in origin. MVD is a major presentation compared to relevant ischaemia due to epicardial CAD. Individual cardiovascular risk assessment in PLWH using CMR may bear a potential for personalised treatment. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The German Centre for Cardiovascular Research (DZHK)